2D nanosheet/3D cubic framework Ni–Co sulfides for improved supercapacitor performance via structural engineering. Issue 24 (8th June 2020) - Zhang, Qi; Shi, Qiqi; Yang, Ye; Zang, Qian; Xiao, Zhenyu; Zhang, Xinghao; Wang, Lei
Abstract : Control construction of 2D nanosheet/3D cubic framework Ni3 S2 /Co3 S4 for high performance supercapacitors. Abstract : The construction of multi-dimensional structured battery-type electrode materials is a promising strategy to develop high performance electrodes for supercapacitors. Herein, a series of battery-type Ni3 S2 @Co3 S4 electrodes with different morphologies are synthesized by controlling the hydrothermal reaction time. Owing to the unique structure with independent but interconnected 2D nanosheets and 3D cubic frameworks, NCS-60 displays high conductivity, numerous active sites and good wettability behavior. It can deliver a high specific capacity of 388.9 mA h g −1 (3500 F g −1 ) at 1 A g −1, an outstanding rate capacity of maintaining 88.6% at 10 A g −1 and long cycle stability. The battery-type supercapacitor hybrid (BSH) device with active carbon (AC) as the negative electrode delivers an energy density of 41.8 W h kg −1 at the power density of 800 W kg −1 . This study provides a feasible route for regulating the morphologies of in situ growth materials that improve the electrochemical performance of supercapacitors.